Marx e i regimi di sussunzione del lavoro - Illuminati, Augusto (Bollettino Filosofico, 2025)
There are two regimes of subsumption of labor to capital, a more general one in which the capitalist puts workers together and extracts absolute surplus value from them without radically altering the pre-existing organization of labor (formal subsumption), a more specific and advanced one (real subsumption) in which the capitalist takes over the organization of labor and subjects it to the logic of the factory and machinery, generating relative surplus value. For Marx, the former precedes the latter, but the two can occasionally coexist. Today, the coexistence of the two subsumptions is widespread, and segments of the working class remain subservient to the rhythms of capital while being formally autonomous, as in platform capitalism (e.g., Uber, food delivery, or Mechanical Turk) in which workers own the means of production. This configuration, along with other factors, intensifies the fragmentation of the working class. Keywords: Class Fragmentation, Clinamen, Formal Subsumption, Platform Capitalism, Real Subsumption